Alliance Structure and the Scope of Knowledge Transfer: Evidence from U.S.-Japan Agreements - Oxley, Joanne; Wada, Tetsuo (Management Science, 2009)
Prior research suggests that equity joint ventures (JVs) are particularly effective vehicles for accessing complex technology. Different schools of thought have emphasized different reasons why joint ventures might support greater knowledge transfer than “bare” license agreements: incentive alignment, organizational embeddedness, and enhanced administrative controls. We probe and refine these theoretical perspectives, drawing out implications of the different theories for the extent and speed of alliance-related knowledge transfer, as well as for knowledge “leakage” in areas not directly related to alliance activities. Using a proprietary data set derived from regulatory filings with the Japanese government we test these implications in our empirical analysis of U.S.-Japan agreements. The picture that emerges from the analysis is one of particularly intense but contained knowledge transfer in equity joint ventures, relative to bare license agreements: knowledge transfers directly related to the alliance activity are enhanced in the JV, and the speed of integration into the Japanese firm's subsequent innovations also increases. In marked contrast, leakage of unrelated technology is significantly reduced. These findings suggest that administrative structures that reduce technology leakage are a key feature of the equity joint venture, a result that is inconsistent with a “pure” knowledge-based perspective on alliances.